Effect of Ground Diatomite on Early Strength of Self-Compacting Mortars - Karabulut, Büşra; Yon, Merve Sahın; Karataş, Mehmet (My University, 2024)
Portland cement fabrication is a significant factor that increases the amount of carbon dioxide released into nature. For this reason, it is very important to use natural and waste materials with pozzolanic properties instead of portland cement. In this article, the usability of diatomite rock, a natural pozzolanic material that can be substituted with portland cement, in the manufacture of self-compacting mortar was studied. In the experimental study, prismatic specimens with dimensions of 40 × 40 × 160 mm were used to examine the impact of ground diatomite on the early age mechanical properties of self-compacting mortar; it was produced by replacing 0%, 5%, 10%, 15%, 20% of diatomite with portland cement, respectively. The slump-flow test to obtain self-compacting mortar was conducted according to the European Federation of Specialized Construction Chemicals and Concrete Systems guidance. Specimens prepared using 0%, 5%, 10%, 15% and 20% diatomite were cured in water at 23±2 ?C temperature for 3 days. 3-day (early age) flexural and compressive strength worths were gained for the samples whose curing period was completed. As a result of this experimental study, it was specified that the highest strengths were in the series containing 5% diatomite, exceeding the reference samples. Additionally, it has been determined that mechanical strength decreases when the diatomite ratio in mixtures is more than 5%.
Keywords: Mechanical properties; Self-compacting mortar; Ground diatomite; Early strength